การใช้บังคับกรมธรรม์ประกันภัยตัวเรือมาตรฐานของสถาบันผู้รับประกันภัยแห่งลอนดอนในประเทศไทย - ธีระพล มิตรประยูร (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objective of this research is to study and analyze whether the Institute of London Underwriters marine hull policy is applicable in Thailand and if it is to what extent. The study deals mainly with three issues : 1) form and content of the marine hull policy under Insurance Against Loss Act B.E. 2535, 2) the marine hull policy under Civil and Commercial Code and under Marine Insurance Act 1906 of England by comparative analysis, and 3) the marine hull policy under Unfair Contract Term Act B.E. 2540. The research findings show that the standard marine hull policy is subject to marine Insurance Act 1906 of England. The Thai court has so far applied the rules of law of this Act as the general principles of law and as the provision most nearly applicable, irrespective of whether they are Thai law. However, the applicability is subject to the laws related to public order or good morals. Moreover, the Thai court has by itself brought the rules of law of this Act into attention for the adjudication of the dispute in marine insurance, in spite of the domestic general principles that foreign laws are the facts which the litigant is required to adduce. Consequently, for the applicability of the marine hull policy in Thailand in the same line as any other countries whether it has foreign elements and for the consistence of the judgements rendered by the Thai court, a specific law in marine insurance should be enacted in Thailand. The Act should cover the entire important issues of marine insurance, including the rule of Warranty, Insurable Interest and Lost or not lost.